"Why Have You Bought a Black Doll?" How Young Children Talk about Diversity. Issue 3 (27th May 2019) - Stockinger, Helena
Abstract: The qualitative Early Childhood research project analyzes how children, aged five to six years, talk about the dimensions of diversity they recognize in their kindergarten and how two kindergartens in Austria deal with diversity. The children talk about age, gender, size, language, religion, different countries of origin, and skin colors. With regard to the kindergarten organization, there is a tendency toward normativity in dealing with some dimensions of diversity. Religious education may contribute to develop safe and brave spaces where differences are allowed and discrimination against children is avoided.